89-81 Court Street, ca. 1870 - Hawes, Josiah Johnson (Tufts Archival Research Center, 2005)
Elevated view northeast of (left to right) 89-81 Court Street, located between Hanover Street to the northwest and Brattle Street to the southeast. Signage adorns the facades of the buildings, which face southwest. Several people stand on Court Street in front of the buildings. 6 13/16 in diameter (image is round), 7 x 7 1/16 overall Photographs